Ethnobotanical of the Lao Isan Ethnic Group in Pho Chai District, Roi Et Province, Northeastern Thailand - Niamngon, Tawanon; Saensouk, Surapon; Saensou, Piyaporn; Junsongduang, Auemporn (Tropical Journal of Natural Product Research (TJNPR), 2024)
Currently, there is urban expansion and development of transportation routes for commercial transportation, and it drives prosperity to rural communities resulting in the villages becoming more prosperous. This may alter the original way of living in harmony with nature, and over time, the knowledge of plant usage passed down through generations may be lost to future generations. Therefore, this study aims to investigate the ethnobotanical practices of the Lao Isan ethnic groups in the area of Na Ngam Village Pho Chai District, Roi Et Province, focusing on their specific uses. Data were collected by interviewing 37 individuals aged 20 years and older between July 2022 and July 2023. Results revealed that there were 317 plant species utilized, belonging to 243 genera and 89 families. These plants were further categorized into 12 groups based on their traditional uses. In the food and spice category, 201 species of plants were used the most, followed by 154 species for medicinal herbs. In terms of the Cultural Important Index, it was found that Oryza sativa had the highest Cl value of 5.35. Meanwhile, constipation syndrome, with the highest Index of 0.93, was associated with Zingiber officinale, which is a medicinal plant with a reported accuracy level (%FL) that covers the most use in treating disease symptoms within this area. Therefore, this knowledge of local wisdom can be considered important and useful information for future generations and can be applied in other scientific fields for sustainable benefits in the future.